Mathematics pocket book for engineers and scientists - Bird, J. O. (Routledge, 2020)
This compendium of essential formulae, definitions, tables and general information provides the mathematical information required by engineering students, technicians, scientists and professionals in day-to-day engineering practice. A practical and versatile reference source, now in its fifth edition, the layout has been changed and streamlined to ensure the information is even more quickly and readily available- making it a handy companion on-site, in the office as well as for academic study. It also acts as a practical revision guide for those undertaking degree courses in engineering and science, and for BTEC Nationals, Higher Nationals and NVQs, where mathematics is an underpinning requirement of the course. All the essentials of engineering mathematics- from algebra, geometry and trigonometry to logic circuits, differential equations and probability- are covered, with clear and succinct explanations and illustrated with over 300 line drawings and 500 worked examples based in real-world application. The emphasis throughout the book is on providing the practical tools needed to solve mathematical problems quickly and efficiently in engineering contexts. John Bird's presentation of this core material puts all the answers at your fingertips.